Marine-derived fungi as biocatalysts - Virués-Segovia, Jorge R.; Muñoz-Mira, Salvador; Durán-Patrón, Rosa; Aleu, Josefina (Frontiers in Microbiology, 2023)
Marine microorganisms account for over 90% of ocean biomass and their diversity is believed to be the result of their ability to adapt to extreme conditions of the marine environment. Biotransformations are used to produce a wide range of high-added value materials, and marine-derived fungi have proven to be a source of new enzymes, even for activities not previously discovered. This review focuses on biotransformations by fungi from marine environments, including bioremediation, from the standpoint of the chemical structure of the substrate, and covers up to September 2022.